The Loneliness of the Long-Distance Principal: Tales from Remote Western Australia - Lock, Graeme; Budgen, Fiona; Lunay, Ralph; Oakley, Grace (Australian and International Journal of Rural Education, 2012)
This research investigated the experience of leadership in an isolated school. Data were obtained through structured and semi-structured interviews (Burns, 2000) with a total of eight principals whose experience of leadership in remote communities ranged from new recruits to several decades. Three research questions guided the investigation: What are the social-biographical characteristics of principals in isolated schools? What are the characteristics of the schools? What are the professional and pedagogical aspects of their current position? The interviews were conducted while the principals were gathered at a central location for professional learning workshops prior to the beginning of a new term. Participation was voluntary with principals who wished to participate making an appointment to meet with an interviewer in a location that afforded the opportunity to speak openly (Wiersma & Jurs, 2009) and with some privacy. The eight principals who elected to be interviewed represented 100% of the principals attending the workshops. The first stage of data analysis involved transcription of the interviews. All responses were then grouped by question, enabling the researchers to see the range of responses to each question. The responses were read and re-read several times in order to establish key themes. The data were then further coded (Cohen, Manion & Morrison 2007) into various sub-themes. Three broad themes, within which the issue of loneliness was identified, emerged from the analysis: affective factors, professional learning, and professional benefits and challenges. Within each of these broad themes a number of sub-themes emerged and are discussed in detail in the paper.